(untitled) (Jurnal Adabiya, 2025)
The development of digital technology demands that Muslims possess adequate digital literacy skills to understand and utilize religious information critically and responsibly. In this context, libraries play a strategic role as digital literacy spaces that provide trusted sources of Islamic information grounded in scholarly traditions. This study aims to examine the role of libraries as digital literacy spaces for Muslims from a contemporary Islamic perspective. The study employed a literature review method with a descriptive qualitative approach through a review of relevant literature. The results indicate that the digital transformation of libraries further strengthens their role in enhancing digital literacy and fostering a moderate and contextual understanding of Islam. Despite challenges such as the digital literacy gap and limited curated collections, digital libraries offer significant opportunities for equitable access to knowledge and the preservation of Islamic scholarly treasures. Perkembangan teknologi digital menuntut umat Islam memiliki kemampuan literasi digital yang memadai agar dapat memahami dan memanfaatkan informasi keagamaan secara kritis serta bertanggung jawab. Dalam konteks ini, perpustakaan memegang peran strategis sebagai ruang literasi digital yang menyediakan sumber informasi keislaman yang tepercaya dan berpijak pada tradisi keilmuan. Penelitian ini bertujuan untuk mengkaji peran perpustakaan sebagai ruang literasi digital umat Islam dalam perspektif Islam kontemporer. Penelitian menggunakan metode studi pustaka dengan pendekatan kualitatif deskriptif melalui penelaahan literatur yang relevan. Hasil kajian menunjukkan bahwa transformasi perpustakaan ke arah digital semakin memperkuat perannya dalam meningkatkan literasi digital serta membangun pemahaman keislaman yang moderat dan kontekstual. Meskipun dihadapkan pada tantangan seperti kesenjangan literasi digital dan keterbatasan koleksi yang terkurasi, perpustakaan digital memiliki peluang besar dalam pemerataan akses pengetahuan dan pelestarian khazanah keilmuan Islam.